Variation of Semen Quality Among Three Generations (F1, F2 and F3) of Holstein Friesian Upgraded Breeding Bulls of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
The experiment was conducted in a well-known private livestock research and development farm in Bangladesh to find out the variation of semen quality parameter among three generations (F1, F2 and F3) of Holstein Friesian upgraded breeding bulls. A total of 312 ejaculates were collected from 6 upgraded breeding bullsthrought the experimental year. The recorded data were summarized using Microsoft Excel 2010 and analyzed using GraphPad Prism 5 softwere. Out of the 312 ejaculates, 273 (87.50%) were found to be creamy in color followed by 26 (8.33%) and 13 (4.17%) as yellowish and watery, respectively. Generation had significant (P0.05) but initial motility and post freezing motility had the significant differences among the three generations. Initial motility ranges from 75.87±0.32 to 78.40±0.38 percent and the post freezing motility ranges from 50.38±0.41 to 52.16±0.43 percent. It could be concluded that most of the semen quality parameters were influenced by generation and freezing. Semen characteristics were better in F2 followed by F3 and F1 generation in upgraded Holstein Friesian bulls.Res. Agric., Livest. Fish.7(3): 457-463,  December 2020